Receptor and ion-channel trafficking - edited by Stephen J. Moss; Jeremy Henley (Oxford University Press, 2002)
This book reviews the recent advances in our understanding of the molecular and cellular mechanisms that control the assembly, transport, targeting and anchoring of the protein complexes making up the most important ion channels and receptor families, fundamental to synaptic function. Improved understanding of these processes is expected to reveal novel therapeutic targets relevant to a range of disease states